Implementation of Legal Protection for the Midwife Profession in Indonesia - Purnomo, Vicki Dwi; Putra , Sarsintorini; Hartini, MC Inge; Kusumaningrum, Anggraeni Endah (Asian Journal of Healthcare Analytics, 2024)
Legal protection for the midwife profession is very important to ensure that they can carry out their duties safely and according to standards. Midwives play an important role in providing health services, especially for mothers and children. However, in practice, they often face legal risks related to malpractice, negligence, or violations of professional ethics. The implementation of legal protection is carried out through regulations and standard operating procedures (SOPs) set by the government and professional organizations. This protection includes preventive legal aspects, such as regulating practice permits, as well as repressive aspects, such as legal assistance if problems occur. These efforts aim to maintain the quality of service and protect the rights of midwives and patients.